Electrically conductive carbon-coated ceramic fiber media - Lee, Jae Chun; Kwon, Hyuk Chun; Kwon, Yong-Pil; Park, Sung; Lee, Hae-Won; Lee, Jong-Ho; Kim, Joosun (SPRINGER, 2006)
Porous ceramic fiber composites were coated with pyrolytic carbon by the decomposition of either propane or infiltrated phenolic resin in a nitrogen atmosphere at 800-900 degrees C. The amount of carbon coating was varied to tailor the electrical conductivity of the carbon-coated composites. The electrical and thermal conductivity of the composites were measured at room temperature using a two-point method and a hot-wire one, respectively. Up to 30 wt% pyrolytic carbon, the electrical conductivity sigma showed linearly increasing tendency and was fitted by the effective conductivity according to the parallel rule of a mixture sigma =Sigma V-i center dot sigma(i) with an effective conductivity of pyrolytic carbon sigma(c) and volume fraction of coated carbon V (c). The electrical conductivity of coated carbons prepared from propane at 900 degrees C and phenolic resin at 800 degrees C was of the order of 10(0) and 10(-1) S cm(-1), respectively.
Keywords: CHEMICAL-VAPOR-DEPOSITION; THERMAL-PROPERTIES; ORGANIC-COMPOUNDS; PHENOLIC RESIN; PYROLYSIS; COMPOSITES; INSULATION; MONOLITHS